Optimal taxation of a monopolistic extractor: are subsidies necessary? - Julien Daubanes (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
In a standard partial equilibrium model of resource depletion, this paper charac- terizes and examines the solution to the optimal taxation problem when extraction is monopolistic. The main result is that the family of subgame perfect effciency- inducing tax/subsidy schemes may include some strict tax policies. This illustrates how the static trade-off between inducing effciency and raising tax revenues in the presence of market power is relaxed under exhaustibility.
Keywords: Q30; L12; H21; 330; Exhaustible resources; Imperfect competition; Optimal taxation; Optimale Besteuerung; Monopolistischer Wettbewerb; Erschöpfbare Ressourcen; Theorie